2021
DOI: 10.1038/s41598-021-99840-6
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for early discrimination between transient and persistent acute kidney injury in critically ill patients with sepsis

Abstract: Acute kidney injury (AKI) is commonly present in critically ill patients with sepsis. Early prediction of short-term reversibility of AKI is beneficial to risk stratification and clinical treatment decision. The study sought to use machine learning methods to discriminate between transient and persistent sepsis-associated AKI. Septic patients who developed AKI within the first 48 h after ICU admission were identified from the Medical Information Mart for Intensive Care III database. AKI was classified as trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 59 publications
1
39
0
Order By: Relevance
“…Advanced machine learning methods are adept at handling high-order interactions and fitting complex non-linear relationships, which can be used to integrate large amounts of data from electronic health records (EHRs). The application of data-driven analytics by machine learning has shown promise to improve predictive performance in medical fields ( 12 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Advanced machine learning methods are adept at handling high-order interactions and fitting complex non-linear relationships, which can be used to integrate large amounts of data from electronic health records (EHRs). The application of data-driven analytics by machine learning has shown promise to improve predictive performance in medical fields ( 12 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prediction models established by these studies were limited by only using the logistic regression method rather than other machine learning models to improve the predictive ability. Moreover, a study including 5984 septic patients with AKI established five prediction models, including logistic regression, random forest, support vector machine, artificial neural network, and extreme gradient boosting to predict persistent AKI [22]. The artificial neural network and logistic regression models achieved the highest AUC of 0.76.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning models have already been applied in many fields, such as outcome prediction [17][18][19], and these models may potentially be used to identify high-risk patients. Machine learning models have been mostly described to predict episodes of the occurrence of AKI during sepsis [20][21][22]. However, there is no study to evaluate their effects on rehospitalization with AKI after patients who survived to discharge from sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…We used clinical indicators to predict the future risk of ESRD by using machine learning models. In previous studies that used AI to predict the progression of renal function, the primary endpoints were the occurrence of AKI or acute kidney disease following ICU admission, cardiovascular surgery, or sepsis [17][18][19]. Nevertheless, the follow-up period of 1-2 years in these studies was too short to effectively assess the long-term eGFR decline or progression to ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…The application of artificial intelligence (AI) in the early prediction and risk stratification of AKI has attracted considerable research attention. Previous studies have demonstrated the use of machine learning algorithms for the early prediction of AKI 48 h after intensive care unit (ICU) admission and for distinguishing between transient and persistent AKI in patients following sepsis or cardiac surgery [17][18][19]. Nevertheless, these algorithms could not predict subsequent ESRD development.…”
Section: Introductionmentioning
confidence: 99%